Analisis Baban Kerja Dengan Kinerja Perawat Di Ruang Rawat Inap Instalasi Pelayanan Kesehatan Jiwa Terpadu RSUD Banyumas - etlida wati; Puput Jeni; Rozali Arsyad Kurniawan (JURNAL KESEHATAN MERCUSUAR, 2023)
Performance is not good an impact on poor service, so that patients feel uncomfortable and dissatisfied with the service. The aim of this research is to analyze the workload and performance of nurses in the Inpatient Department of the Integrated Mental Health Services Installation at Banyumas Regional Hospital. This type of quantitative research with a correlational study design. The sampling technique was total sampling with a total of 46 nurses in the Inpatient Department of the Integrated Mental Health Services Installation at Banyumas Regional Hospital. The research instrument used a questionnaire. Data analysis used the Spearman rank test. The results showed that most of the nurses' workload was in the medium category (52.2%), most of the nurses' performance was in the good category (54.3%). The relationship between workload and nurse performance in the Inpatient Department of the Integrated Mental Health Services Installation at Banyumas Regional Hospital obtained a p value of 0.000 ? 0.05 and rho value: -0.614. Conclusion: There is a relationship between workload and the performance of nurses in the Inpatient Department of the Integrated Mental HealthServices Installation at Banyumas Regional Hospital.